2011
DOI: 10.1007/s00216-011-5482-5
|View full text |Cite
|
Sign up to set email alerts
|

Composite nanoparticles: the best of two worlds

Abstract: Nanomaterials have rapidly moved into the mainstream for chemical and biological analysis. Nanoparticle probes enhance signal intensity, increase the chemical and physical stability of the probe, and facilitate surface modification for specific targeting. Unfortunately, common problems are encountered with many nanoparticle probes, e.g., poor solubility, poor biocompatibility, and leakage of encapsulated components, that severely restrict the application of probes to ex vivo samples under carefully controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The combination of several materials in one multi-component particle, such as core-shell or hybrid structures, allows for the fabrication of nanoplatforms that overcome the limitations of single-component structures. In fact, composites often possess superior solubility and biocompatibility compared to individual materials [44]. While silica coatings prevail in the field of inorganic-inorganic composites [45,46], combinations of, e.g., silicon nanostructures modified with metal or metal oxide nanoparticles have recently demonstrated highly interesting properties for biosensing applications [47].…”
Section: Composite Npsmentioning
confidence: 99%
“…The combination of several materials in one multi-component particle, such as core-shell or hybrid structures, allows for the fabrication of nanoplatforms that overcome the limitations of single-component structures. In fact, composites often possess superior solubility and biocompatibility compared to individual materials [44]. While silica coatings prevail in the field of inorganic-inorganic composites [45,46], combinations of, e.g., silicon nanostructures modified with metal or metal oxide nanoparticles have recently demonstrated highly interesting properties for biosensing applications [47].…”
Section: Composite Npsmentioning
confidence: 99%
“…The advent of biocompatible nanoarchitectures has contributed significantly to a broad range of biomedical applications including biosensing, 18 drug delivery, 1,7,916 and diagnostic imaging. 1,12,13,1724 A highly diverse catalog of nanomaterials has been prepared from inorganic, polymeric and hybrid materials in a multitude of geometric configurations.…”
Section: Introductionmentioning
confidence: 99%
“…1,12,13,1724 A highly diverse catalog of nanomaterials has been prepared from inorganic, polymeric and hybrid materials in a multitude of geometric configurations. Among the most promising geometries for intracellular sensing and delivery is the recent advent of silica and polymer nanoshells.…”
Section: Introductionmentioning
confidence: 99%
“…Composite particles of QDs and metal NPs have spurred a great deal of interest among researchers. [27][28][29] For example, Liu et al 30 developed an Au/TiO 2 hybrid mesoporous lm sensitized by CdSe QDs for photoelectrochemical applications. The CdSe QDs were deposited on the TiO 2 NP lm of the Au/TiO 2 hybrid structures by chemical bath and the results showed that the photocurrent of the TiO 2 lm was signicantly enhanced by the Au NPs.…”
Section: Labels For Analytementioning
confidence: 99%